The historical nature of the legal tradition - Ilyn L. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького)
Purpose. The study aims to analyze the historical nature of legal tradition, determine its essence as a determinant reflecting the socio-cultural, economic, and political conditions of its time, and reveal its role in the formation and development of modern legal systems. Method. The article uses a comprehensive methodological approach, including the historical method for analyzing the development of legal tradition in different historical periods, the comparative method for comparing legal systems of other countries, the sociological method for studying the impact of legal traditions on society, and the systematic approach for studying legal tradition as a holistic phenomenon. Results. The author establishes that legal tradition is a vital element of the national legal system, ensuring its stability, continuity and cultural identity. Preserving legal tradition as a dynamic phenomenon capable of developing and adapting to modern challenges is the key to creating a harmonious legal environment. The synthesis of historical experience and modern reforms will allow Ukraine to create an effective, stable, and competitive legal system that meets European standards and ensures the rule of law. At the same time, the need to eliminate the negative vestiges of Soviet law, such as the administrative-command style of governance, legal nihilism, corruption, formalism, and disregard for the rule of law, can be considered a challenge. To overcome these challenges, it is necessary to implement systemic reforms and adapt the best historical elements of the Ukrainian legal tradition. Scientific novelty. The author establishes that legal tradition plays a crucial role in ensuring the continuity of legal systems. It reveals its importance as a mechanism for preserving the socio-cultural identity of law and proves its vital role in adapting modern law to global challenges. Practical significance. The results of the study can be used in further historical and legal research and in the preparation of special courses.